INFLUENCE OF MECHANICAL STIMULATION ON BONE TISSUE ELASTICITY WITH FEM - Khusnul Yakin (Jurnal Neutrino: Jurnal Fisika dan Aplikasinya)
Mechanical stimuli have a significant influence on the growth of bone. Osteocytes of canaliculi can communicate with osteoblasts. Furthermore, osteoblasts communicate with cells in the bone marrow with projecting it cells into endothelial thus forms new bone cells. This aims of this research are to determine the effect of mechanical stimuli on the static and dynamic of stress, strain, and strain rate on the bone tissue and the influence of differences in bone properties (Young’s modulus). In this research, a linear elastic material model was chosen for bone tissue modelling and analysis. The strain and stress of the modelling bones were calculated using finite element method of the derivation harmonic oscillator for bone. The results showed that the static force results maximum strain rate  20.986/s, furthermore, due to the different properties of the bone (reduction is 6% of Young’s modulus of 17.9 GPa to 16.92 GPa ) resulted in the increase strain rate 0.238/s.The increase in external force is proportional to the increase in the maximum strain and strain rate. The decrease bone properties (reduction is 6% of Young’s modulus) decreases the tension 2.36%, raise the strain 14.536% or every decrease 2% (the increase is one decade of age) will decrease tension 0.78667% and the increase the strain 4.485%. The results of this study can be used to calculate the bone density by using the equations of  V. Klika and F. Marsik. Besides, this analyze study also useful for modelling the growth of bone around the joints in the spine.